COVID-19 Policy Response Notes for Vietnam - World Bank (World Bank, Hanoi, 2020)
‘You can count on your trusted friends in difficult time’. This saying symbolizes Vietnam and the World Bank Group’s long-lasting partnership over the past 25 years, which grows even stronger during difficult times in Vietnam or in the global economy. This has been verified once more during the COVID-19 crisis. Today, Vietnam’s timely and evidence-based response has led to tremendous success in containing the COVID-19 outbreak, with just over 300 positive cases and no deaths. The enviable success story has been applauded across the globe, and the country’s experience has been recently shared by Prime Minister Nguyen Xuan Phuc at the 73rd World Health Assembly organized on May 18-19, 2020. Vietnam’s successful management of COVID-19 has also been extended to the economy, so much that Vietnam is now projected to be one of the few world’s fastest growing countries in 2020. Since the beginning of the COVID-19 pandemic, the World Bank has shared a series of five policy notes with Vietnamese policymakers. These just-in-time notes have supported the Government in its efforts to monitor the current crisis and helped it sequentially to formulate policy responses from the health crisis management through stimulating the recovery of the economy. These notes built on expertise from around the globe, including Hanoi, Washington, DC and beyond. The diagnostics and recommendations stem from the deep dialogue that our experts have fostered with government officials and other stakeholders in Vietnam over the years. They also benefited from expertise based on successes and lessons learned in other countries.